Study of Rice Cultivation Planted In Elliptical Silukah Sycamore District Sijunjung Regency Sijunjung - Fitria, Desmi; Rianto, Slamet; U, Iswandi (STKIP PGRI Sumbar, 2013)
Rice planting is a way of intensive rice cultivation and efficient with the process management system based on the processing of roots with soil, plants and water, and other elements of agroecosystems. This study aims to determine : 1) how to land management, 2) how to seed selection, 3) planting, 4) means fertilization, 5) maintenance way of planting rice in elliptical Silukah district Sijunjung regency Sijunjung. This research is descriptive. The population is a group of farmers in Silukah ellipse with the number 125. Samples taken with proportional random sampling technique with the proportion of 50 %, so the total sample of 63 people. Techniques of data collection through questionnaire or instrument. The data analysis using the percentage formula. The research found that: 1) how to land management including categories with a percentage of 53.97 %, 2) how the selection of seeds including category less well with the percentage of 38.09 %, 3) planting including unfavorable category with a percentage of 44.48 %, 4) means fertilization including unfavorable category with the percentage of 33.97 %, 5) the way of maintenance, including categories with a percentage of 56.32 %.